CORRIDOR AS A SUSTAINABLE SOCIAL SPACE IN HIGH-RISE RESIDENTIAL BUILDING - Yuli Kalson Sagala; Rully Damayanti; Rony Gunawan Sunaryo (Advances in Civil Engineering and Sustainable Architecture, 2022)
The rapid population growth and limited land on earth make high-rise residential buildings, especially in urban areas, inevitable. However, from several studies and analyses, many of these vertical living did not / have not fulfilled social sustainability aspects, which are essential aspects of the three spheres of sustainability concepts, namely social sustainability, economic sustainability, and environmental sustainability. Therefore this study will emphasize creating sustainable social space in high-rise residential buildings but will focus more on Corridor.Corridor as a definite area and always exist in high-rise residential building, have a high frequency always to be used and passed by residents as the main circulation path from and to the unit of residence. Therefore Corridor has great potential to influence the lives and way of life of the residents. Therefore, if we as architects can propose a design intervention by including consideration of the rules of the social space parameters, the Corridor can be an ideal sustainable social space that is needed and can be positively beneficial for residents, so that in the long run, it can help achieve Sustainable Architecture.